Clinical manifestations of peripheral nervous system involvement in human chronic chagas disease Manifestaciones clinicas de compromiso del sistema nervioso periférico en el estádio crônico de la enfermedad de Chagas - Osvaldo Genovese; Carlos Ballario; Ruben Storino; Elsa Segura; Roberto E. R. Sica (Arquivos de Neuro-Psiquiatria)
We conducted a clinical and electromyographical study in patients with Chagas' disease in the indeterminate or chronic stages of the illness. Altogether 841 patients were examined. Only 511 were admitted within the protocol; the remainder patients were rejected because they showed other causes able to damage the nervous system. Fifty two (10.17%) out of the 511 patients showed signs and symptoms of peripheral nervous system involvement in the form of sensory impairment and diminished tendon jerks suggesting the presence of neuropathy. Forty five of them were submitted to a conventional electromyographical examination. Fifteen of mem showed normal results, while the remainder 30 disclosed a reduced interference pattern, being most of the remaining motor unit potentials fragmented or poliphasic, reduced sensory and motor conduction velocities and diminished amplitude of the sensory action potential. The findings suggest that some chagasic patients in the indeterminate or chronic stages of the disease may develop a clinical mild sensory-motor peripheral neuropathy. El estúdio presente fue diseftado con ei objeto de pesquizar Ia existência de manifestaciones clinicas en pacientes afectados por enfermedad de Chagas, en estádio indeterminado o crônico, que tuviesen, ai menos, 2 reacciones serologicas positivas. En total fueron examinados 841 enfermos. De ellos solo 511 fueron admitidos en ei protocolo; los restantes fueron rechazados por mostrar Ia presencia de otras causas que hubiesen podido danar su sistema nervioso. Dentro de los 511 pacientes admitidos, 52 (10.17%) evidenciaron alteraciones objetivas y subjetivas de Ia sensibilidad y disminucion de los reflejos osteotendinosos. Estos signos y sintomas, que sugieren la presencia de neuropatia, podian combinarse de diferente manera. Como complemento dei examen clinico, se efectuo estúdio electromiografico convencional en 45 de estos pacientes. En 15 los hallazgos fueron normales, en tanto que en los restantes 30 pudo demostrarse reduccion de la capacidad de reclutamiento voluntário de unidad motora, presencia de potenciales de unidad motora fragmentados o polifasicos, reduccion de la velocidad de conduccion motora y sensitiva y disminucion de la amplitud dei potencial sensitivo. Los resultados obtenidos sefialan que una proporcion de los pacientes en el estádio indeterminado o crônico de la infeccion pueden desarrollar una moderada neuropatia sensitivo-motora con expresion clinica.